Hospital emergency suitability protocol: translation and adaptation to the Brazilian culture - Rouslanny Kelly Cipriano de Oliveira; Ana Maria Ribeiro dos Santos; Julyanne dos Santos Nolêto; Guilherme Guarino de Moura Sá; Raylane da Silva Machado; Márcia Teles de Oliveira Gouveia; Maria Zélia de Araújo Madeira (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective Translate and culturally adapt the Hospital Emergency Suitability Protocol (HESP) to Brazilian Portuguese. Method Methodological study, developed from 2019 to 2021, in an emergency hospital, and which followed the stages of translation, synthesis of translations, back-translation, review by an expert committee, pre-test and submission to the authors of the protocol. The sample included four translators, five experts, who assessed conceptual, semantic, cultural, and idiomatic equivalence, 21 nurses and nine physicians, who participated in the pre-test. Content Validity Index (CVI), Cronbach's alpha and Kendall's coefficient of concordance were used. Results The final version of the adaptation presented Content Validity Index that ranged from 0.40 to 1.0. The internal consistency, according to Cronbach's alpha coefficient, showed Semantic Equivalence (α=0.815), Idiomatic Equivalence (α=0.924), Experiential Equivalence (α=0.682), Conceptual Equivalence (α=0.71), which presented acceptable values, except for the experiential equivalence. Kendall W's coefficient (W=0.14 to 0.58) revealed good reliability. Conclusion The translation and cultural adaptation process of the HESP originated an instrument applicable to the Brazilian context.